The Implicature and Presupposition Analysis of “Fever” Song Lyrics by Adam Lambert - Hidayat, Arif; Mujani, Sahril; Wahab, Bizrinov R (STIBA IEC JAKARTA, 2025)
The research aims to explore the usage and meanings of these elements in the lyrics by analyzing each sentence and describing them using a semantic and pragmatic method. The study also discusses the influence of music genres on the listener’s mood and emotions. The research findings shed light on the cognitive processes involved in counterfactual thinking and the online processing of counterfactual conditionals. The study’s emphasis on textual analysis and interpretation aligns with the qualitative descriptive model, providing a detailed understanding of implicatures and presuppositions in the song lyrics. The research contributes to understanding the role of linguistic representations in contributing to pragmatic presuppositions and the derivation of soft triggering. Overall, this research provides insights into the cognitive mechanisms underlying the comprehension of counterfactual statements and the significance of music genres in shaping the listener’s emotions and sentiments.